1968
DOI: 10.1172/jci105861
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of thyroxine-binding prealbumin to the binding of thyroxine in human serum, as assessed by immunoadsorption

Abstract: A B S T R A C T An immunoadsorption technique employing a rabbit antiserum specific for human serum prealbumin has been devised to remove thyroxine (T4)-binding prealbumin (TBPA) from serum completely without affecting the T4 -binding activity of thyroxine-binding globulin (TBG) or the concentration of the other major proteins in serum. As judged from the proportion of T4 associated with the antigen-antibody precipitate, only about 15% of the endogenous T4 is bound by TBPA, a value considerably less than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
2
2

Year Published

1978
1978
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 159 publications
(76 citation statements)
references
References 22 publications
(14 reference statements)
0
72
2
2
Order By: Relevance
“…Together, the studies referred above suggest that the relevance of TTR is more than that initially described, as a carrier of T 4 and retinol. Throughout time, studies addressing the identification of novel TTR ligands were performed to explore the biology of the protein.…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Together, the studies referred above suggest that the relevance of TTR is more than that initially described, as a carrier of T 4 and retinol. Throughout time, studies addressing the identification of novel TTR ligands were performed to explore the biology of the protein.…”
Section: Introductionmentioning
confidence: 77%
“…In the case of TTR, studies with TTR knockout (KO) mice suggested that TTR is not required for normal T 4 tissue uptake or distribution, and that its absence does not impair hormone tissue contents, despite the low circulating levels of total T 4 (16,17). These observations reinforced the idea that TTR is not necessary for the metabolism of T 4 and are in agreement with the free hormone hypothesis for T 4 uptake (18), in which the hormone biological activity depends only on its free plasma concentration. On the other hand, it was reported that T 4 distribution from the CSF into the brain is TTR-dependent and occurs via receptor-mediated endocytosis (19).…”
Section: Is Ttr a Relevant Carrier Of T 4 ?mentioning
confidence: 95%
See 2 more Smart Citations
“…Transthyretin (TTR), plasma protein primarily synthesized in the liver, choroid plexus and in retinal pigment epithelium, is the basic transporter of thyroxine and retinol-binding protein in mammals [Goodman, D., 1987;Woeber & Ingbar, 1968]. Three human diseases are characterized by extracellular transthyretin deposits -Familial Amyloidotic Polyneuropathy (FAP), Familial Amyloidotic Cardiomyopathy (FAC) and Senile Systemic Amyloidosis (SSA).…”
Section: Drosophila Model For Transthyretin-associated Amyloidosismentioning
confidence: 99%